Impaired glucose metabolism underlies articular cartilage degeneration in osteoarthritis. Issue 6 (24th May 2022) - Li, Ke; Ji, Xing; Seeley, Rebecca; Lee, Wen‐Chih; Shi, Yu; Song, Fangfang; Liao, Xueyang; Song, Chao; Huang, Xiaobin; Rux, Danielle; Cao, Ju; Luo, Xiaoji; et al.
Abstract: Osteoarthritis (OA) is the leading joint disease characterized by cartilage destruction and loss of mobility. Accumulating evidence indicates that the incidence and severity of OA increases with diabetes, implicating systemic glucose metabolism in joint health. However, a definitive link between cellular metabolism in articular cartilage and OA pathogenesis is not yet established. Here, we report that in mice surgically induced to develop knee OA through destabilization of medial meniscus (DMM), expression of the main glucose transporter Glut1 is notably reduced in joint cartilage. Inducible deletion of Glut1 specifically in the Prg4‐expressing articular cartilage accelerates cartilage loss in DMM‐induced OA. Conversely, forced expression of Glut1 protects against cartilage destruction following DMM. Moreover, in mice with type I diabetes, both Glut1 expression and the rate of glycolysis are diminished in the articular cartilage, and the diabetic mice exhibit more severe cartilage destruction than their nondiabetic counterparts following DMM. The results provide proof of concept that boosting glucose metabolism in articular chondrocytes may ameliorate cartilage degeneration in OA.